Synthesis and evaluation of antiviral, antitubercular and anticancer activities of some novel thioureas derived from 4-aminobenzohydrazide hydrazones [4-Aminobenzohidrazit hidrazonlarından türetilmiş bazı yeni tiyoürelerin sentezi, antiviral, antitüberküler ve antikanser etkilerinin deǧerlendirilmesi] - KÜÇÜKGÜZEL, İLKAY; SÜZGÜN, PELİN; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (Marmara University, 2010)
A series of novel 1-[4-[[2-[(4-substituted phenyl)methylene]hydrazino]carbonyl]p henyl]-3-substituted thiourea derivatives have been synthesized by the addition of substituted aryl isothiocyanates to 4-amino-N'-[(4-substituted phenyl) methylene] benzohydrazide, which was prepared by condensation of 4-aminobenzoic acid hydrazide with 4-fluorobenzaldehyde or 4-(trifluoromethyl)benzaldeyde. All synthesized compounds were evaluated in vitro against HIV-1 (IIIB) and HIV-2 (ROD) strains in MT-4 cells, as well as other selected viruses such as HSV-1, HSV-2, Coxsackie virus B4, Sindbis virus, human cytomegalovirus, and varicella-zoster virus using HeLa, Vero, or HEL cell cultures. Antimycobacterial activity against Mycobacterium tuberculosis H37 Rv was also evaluated. The anticancer activity and cytotoxicity screening of the synthesized compounds were determined on A 549 and L 929 cell lines.
Keywords: Anticancer activity; Antiviral activity; Hydrazones; Mycobacterium tuberculosis H37Rv; Thioureas